A dramatic conformational effect of multifunctional zwitterions on zeolite crystallization. Issue 93 (9th November 2020) - Dong, Lei; Zhai, Dong; Chen, Zhuwen; Zheng, Guangchao; Wang, Yanding; Hong, Mei; Yang, Shihe
Abstract : Carnitine functions as a mesoporogen in LTA zeolite synthesis whereas acetylcarnitine acts as a crystal growth modifier. Experimental and theoretical studies reveal a remarkable effect of molecular conformation on the roles of organic functional groups during zeolite crystallization. Abstract : Carnitine functions as a mesoporogen in LTA zeolite synthesis whereas its structural analogue acetylcarnitine acts as a crystal growth modifier. An array of experimental and theoretical studies reveal a remarkable effect of molecular conformation on the actual roles of organic functional groups during zeolite crystallization.